2012
DOI: 10.1002/acs.2331
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive observer for a class of nonlinear systems with time‐varying delays

Abstract: The adaptive observer design problems have been extensively studied in literature for both linear and nonlinear systems. Some researches have also been carried out on adaptive observer design for linear time-delay systems, but there is no significant work on adaptive observer design for nonlinear time-delay systems. In this work, the adaptive observer design problem for a class of nonlinear time-delay systems is considered. The observer is designed for the nonlinear systems whose nonlinear functions satisfy Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…As is well known, both uncertainty and time delay are often encountered in many practical control systems. Therefore, the robust control problem for uncertain time-delay systems has attracted a considerable amount of interests, and the adaptive control method is one of the effective ways to deal with the uncertain problem [1][2][3][4][5][6][7][8][9][10][11][12]. However, it is worth pointing out that the above mentioned results are infinite-time ones.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, both uncertainty and time delay are often encountered in many practical control systems. Therefore, the robust control problem for uncertain time-delay systems has attracted a considerable amount of interests, and the adaptive control method is one of the effective ways to deal with the uncertain problem [1][2][3][4][5][6][7][8][9][10][11][12]. However, it is worth pointing out that the above mentioned results are infinite-time ones.…”
Section: Introductionmentioning
confidence: 99%
“…Although this topic has been extensively investigated in the literature, from both a theoretical and a practical perspective (see the papers [19]- [25] and [28]- [32]), only the most important results provided by the authors in the last 20 years are reported here, based on the so-called Luenberger-like observers, in praise of Luenberger seminal work [2]. The delay free case was originally proposed in [3], [4] and it has been subsequently extended to the case of large constant output delays [5], bounded [6] or unbounded [7] time-varying output delays, and also to systems with state delays [8], [9].…”
mentioning
confidence: 99%
“…In addition, a simultaneous state and disturbance estimator was proposed in [16] for time-delay continuous systems with application to fault diagnosis and fault tolerance. It is noted that all the results in [12][13][14][15][16] were focused on state delayed systems rather than output delayed systems.In many engineering systems, the output measurements are often subjected to non-negligible time delays. As a matter of fact, this type of time-delay occurs when the measured output data are transmitted via a low speed communication system.…”
mentioning
confidence: 99%
“…By using linear matrix inequality technique, a robust observer was presented in [14] for nonlinear discrete-time systems with time-delays. In [15], an adaptive observer was addressed for Lipschitz nonlinear systems with time-varying delays. In addition, a simultaneous state and disturbance estimator was proposed in [16] for time-delay continuous systems with application to fault diagnosis and fault tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation